If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -42) = x Reorder the terms: (-42 + 5x) = x Remove parenthesis around (-42 + 5x) -42 + 5x = x Solving -42 + 5x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -42 + 5x + -1x = x + -1x Combine like terms: 5x + -1x = 4x -42 + 4x = x + -1x Combine like terms: x + -1x = 0 -42 + 4x = 0 Add '42' to each side of the equation. -42 + 42 + 4x = 0 + 42 Combine like terms: -42 + 42 = 0 0 + 4x = 0 + 42 4x = 0 + 42 Combine like terms: 0 + 42 = 42 4x = 42 Divide each side by '4'. x = 10.5 Simplifying x = 10.5
| 50+15x=50 | | 5[-3(4x+3)+5(3x-2)]= | | 1000=(30+x)(15+x) | | 14-2x+4x=72 | | 10=-5(x-5) | | 2r-(5+-r)=13+2r | | 3x-(x+1)=-2+5(x-4) | | 0.9x=.2 | | =x^4-6x^2+9 | | -33=16x+15 | | (x+10)=360 | | [4x-8]-3x=6x+2 | | 8x+22+9=19 | | .2(60)+0.05=.1(60+x) | | 1.3x+2.8=3.2x-1 | | 22=x+2+10 | | (4-w)=3(2w+2) | | 8-abs(1-3x)=-1 | | 2x^2+7=7x | | 22=22+2+10 | | 75=-5[4x+1] | | -1x=4x-3 | | 5z(z-2)+3z(z+4)= | | 7n+7=5(-5-5n) | | 22=2+10 | | 3x+18+12x-9=5x-2 | | 6y+9=3(2y-3) | | X^4-3x^3-12x^2=0 | | 6(5x+4)+3(2x+6)+5=36x+48 | | -0.87y+2=y-0.6 | | -40=-8(8-m) | | -6(x-9)=-42 |